Praktik Samsarah dalam Transaksi Kendaraan Bermotor: Analisis Kesesuaian Akad Ijarah Desa Nambah Rejo Kota Gajah - Sopia Icha Maharani; Hotman Hotman; Suraya Murcitaningrum (Masyarakat Ekonomi Syariah Bogor, 2026)
Intermediary practices in buying and selling transactions are known in Islamic economics as samsarah, referring to a service that connects sellers and buyers in exchange for compensation. This study aims to analyze the practice of samsarah in motor vehicle transactions in Nambah Rejo Village and to examine the mechanism of fee determination from the perspective of the ijarah contract. The study employs a qualitative approach using field research. Data were collected through interviews, observations, and documentation involving brokers, sellers, and buyers of motor vehicles. The findings indicate that samsarah functions as an intermediary that facilitates communication and negotiation processes until a transaction agreement is reached. The amount of the fee does not have a fixed standard and is often determined solely based on verbal agreements among the parties. While the practice generally fulfills most of the pillars of the ijarah contract, in several cases there remains ambiguity in determining the ujrah (fee), which may potentially give rise to elements of gharar.